VD_FINDINFO AP / 2011 / 23 vom 2. Februar 2011 - VD Tribunal cantonal (2011)
CESSION DE CRÉANCECO, PROROGATION DE FOR, COMPÉTENCE RATIONE LOCI | 164 al. 1 CO, 164 CO, 170 CO, 452 al. 1ter CPC, 452 al. 2 CPC, 452 CPC, 60 CPC, 9 al. 1 LFors, 9 LFors, 405 al. 1 CPC (CH)